LA CORRÉLATION ENTRE LES MYTHES DE LA DÉMOCRATIE RACIALE ET DE LA CORDIALITÉ DANS LA FORMATION DE L’IDENTITÉ BRÉSILIENNE – DISCRIMINATIONS POSITIVES ET QUOTAS SOCIAUX - Poullet, Yves; Kaufmann, Roberta Fragoso Menezes (Revista da AJURIS, 2023)
THE CORRELATION BETWEEN THE MYTHS OF RACIAL DEMOCRACY AND CORDIALITY IN THE FORMATION OF BRAZILIAN IDENTITY – POSITIVE DISCRIMINATION AND SOCIAL QUOTAS DOMAINE(S): droit constitutionnel; droits humains. RÉSUMÉ: L’article analyse de quelle façon la compréhension de l’inégalité sociale légitime une politique brésilienne proactive visant l’inclusion des plus pauvres. En particulier, le propos entend vérifier jusqu’à quel point la construction des mythes de l’homme cordial et de la démocratie raciale au Brésil est perçue comme un obstacle à la construction de l’égalité des citoyens. ABSTRACT: The article analyzes how the understanding of social inequality legitimizes a proactive Brazilian policy aimed at the inclusion of the poorest. In particular, the article intends to verify to what extent the construction of the myths of the cordial man and racial democracy in Brazil is perceived as an obstacle to the construction of the equality of citizens. MOTS-CLÉS: racisme; démocratie raciale; homme cordial; proactivité politique, discriminations positives et quotas sociaux. KEYWORDS: racism; racial democracy; cordial man; political proactivity, positive discrimination and social quotas. RÉSUMÉ: 1 Introduction; 2 De l’importance des mythes de «l’homme cordial et de la «démocratie raciale» comme fondateurs de l’identité brésilienne; Conclusions; Références. SUMMARY: 1 Introduction; 2 On the importance of the myths of “the cordial man and of “racial democracy” as founders of Brazilian identity; Conclusions; References.